A Study of Pituitary Macroadenoma Transnasal Endoscopic Excision (Indian Journal of Public Health Research & Development, 2025)
Background: Pituitary macroadenomas are typically benign tumors over 10mm in size, originating from glandular tissue in the pituitary gland. Understanding tumor consistency is crucial for determining the surgical approach. Imaging, especially MRI, helps assess tumor size, extent, and consistency, which influence the ease of resection, success, and complication risks.Aim:To study the presentation, radiological evaluation, surgical technique, complication and management of pituitary macroadenoma.Materials and Methods:This observational study was conducted at a tertiary care hospital in Chennai from March to September 2016, involving 28 patients with pituitary macroadenomas. Data on demographics, tumor type, presentation, consistency (from MRI T2-weighted images), intraoperative findings and complications, along with their management were collected and analyzed using descriptive statistics.Results:Of the 28 cases, 17(60.7%) were nonsecretory, and 11(39.3%) were secretory. Common symptoms included headaches (71.4%) and visual defects (42.8%). MRI revealed 46.4% of tumors were solid, 35.7% semisolid, and 17.9% cystic, with 50% extending to the suprasellar region. Surgical findings indicated that most solid tumors (92.3%) were firm, 60% of semisolid tumors were soft and 40% were firm , while cystic consistency matched MRI predictions. The most common postoperative complication was diabetes insipidus in 3 cases (10.7%).Conclusion: Pituitary macroadenomas were most common in the 5th decade. Nonsecretory tumors were more common, particularly in females, while secretory tumors were more prevalent in males. MRI was useful tool in predicting tumor consistency, and the transsphenoidal endoscopic approach was effective for removing cystic and soft macroadenomas.
Keywords: Pituitary Macroadenoma, Magnetic Resonance Imaging, Transnasal endoscopic excision